The impact of economic growth, inequality, and resource depletion on CO2 emissions in Indonesia: Evidence from the ARDL model - Annisa, Annisa; Yulianita, Anna; Bashir, Abdul (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2025)
This study examines the impact of natural resource depletion, economic growth, and income inequality on CO₂ emissions in Indonesia from 1990 to 2021. Utilizing time series data from the World Bank, the analysis employs the Auto-Regressive Distributed Lag (ARDL) model to simultaneously assess both short- and long-run relationships among the variables, while also testing the validity of the Environmental Kuznets Curve (EKC) hypothesis. The results reveal that natural resource depletion, economic growth, and income inequality all have a positive and statistically significant effect on CO₂ emissions in both the short and long term. Furthermore, the findings provide strong empirical support for the existence of an inverted U-shaped EKC in Indonesia, indicating that emissions initially rise with income but eventually decline beyond a certain income threshold. These results underscore the crucial need for comprehensive policy frameworks that effectively integrate economic development, environmental sustainability, and social equity. In particular, the significant role of resource depletion necessitates prioritizing sustainable resource management strategies—such as forest conservation, responsible mining practices, and improved resource efficiency—to mitigate environmental degradation.